Analisis Potensi Sanitary Landfill Pada TPA Randegan Kota Mojokerto - Rafli Rudini, Mochammad (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The rapid population growth in Mojokerto City has led to an increase in daily solid waste generation, averaging ±80 tons per day. Currently, Randegan Landfill, with an area of ±6.05 hectares, operates under a controlled landfill system that has not been fully effective in minimizing environmental impacts. This study aims to analyze the potential implementation of a sanitary landfill system as an alternative waste management strategy at Randegan Landfill. The research method involved literature review, collection of primary data on waste generation, and secondary data on landfill conditions. The findings indicate that household waste contributes the largest proportion (77.5%), with organic waste dominating the composition (75%). The application of sanitary landfill, supported by essential elements such as lining systems, leachate collection, gas ventilation, and monitoring systems, is expected to reduce environmental pollution, improve waste management efficiency, and provide opportunities for energy recovery through methane gas utilization. The study concludes that transitioning from controlled landfill to sanitary landfill is an urgent necessity for Mojokerto City, requiring appropriate land allocation, strong policy support, and collaboration among stakeholders to ensure sustainable waste management.